A Dual-Transformer Series Resonant Converter With Wide ZVS Range and Minimized RMS Current Operation - Yinan Li; Song Hu; Chuan Sun; Peiwen Li; Wanlin Nie; Huiqing Wen; Akshay Rathore; Xiaodong Li (IEEE Open Journal of Industry Applications)
To improve the operation efficiency under various conversion gains, a series resonant dc–dc converter is proposed in this article for renewable power generation application, which adopts a dual-transformer structure and employs an asymmetrical modulation scheme. First, the operation principle of the converter and the modulation scheme is analyzed. As a result, the steady-state characteristics expressions are solved, including the resonant tank current and transmission power. To reduce the high-frequency switching loss, the additional parameter of dual-transformer structure, which is defined as the ratio of two high-frequency transformers, can be tuned to widen zero-voltage switching (ZVS) range on both sides. Furthermore, Lagrange multiplier method is applied to minimize the root mean square (rms) current to reduce the conduction loss. With full ZVS range operation and minimized rms current, the overall efficiency of the proposed converter can be enhanced. Finally, the performance of the proposed converter with the adopted control scheme is evaluated with the experimental results on a 400 W lab prototype converter.